(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This review article analyzes the process of developing primary health care through the implementation of digital technologies. The article focuses on examining the current state of practice, existing challenges in this area, and mechanisms for improving efficiency. Within the scope of the study, the theoretical foundations of digital transformation, the level of implementation in various countries and organizations, the functional capabilities of health information systems, and the factors influencing their adoption are systematically analyzed.